Scoping Review: Implementation of Quality Management System Model and Anti-Bribery Management System at Inkindo Jatim in Improving Integrity and Performance of Government Construction Consulting Projects - Arif Wahono; Sutanto Hidayat; Iftitah Ruwana; Nanta Sigit (International journal of technology and education research, 2025)
The implementation of SIMMAP aims to produce a documented, transparent work process and reduce risk deviations. From a management strategy perspective, INKINDO's SIMMAP can be seen as an institutional instrument that strengthens the position of consulting firms in a value- and integrity-based government procurement system. With consistent and sustainable implementation, SIMMAP is expected to be able to become an organizational transformation tool that is adaptive to regulatory changes, transparency demands, and the competitiveness of the national and international construction services market. The SIMMAP Version 01 web application supports the implementation of a Quality Management and/or Anti-Bribery Integration System, facilitating document management for business entities. After registering, company admins can create child accounts according to quality management/anti-bribery standards. With an affordable subscription fee, SIMMAP users can also join a community to discuss and share implementation experiences, both for success stories and problem solving. SIMMAP provides online/offline usage support.